PENGARUH BIAYA PENDIDIKAN, BIAYA PELATIHAN DAN BIAYA PROMOSI TERHADAP TINGKAT PENJUALAN PADA SEKTOR ROKOK (STUDI KASUS PT. GUDANG GARAM. TBK) - Dewi, Ririn Sari; Rahmawati, Titah; Mu’arifin, Hidayatul (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to analyze the effect of education, training, and promotion costs on the level of sales at PT Gudang Garam Tbk. The research method used is hypothesis testing using multiple linear regression. The data used in this study is the financial data of companies listed on the stock exchange. The analysis results show that training costs influence sales but are not significant. This is indicated by a significance value of 0.619, more significant than the significance level of 0.05 (5%). In addition, advertising costs also influence sales with a significance value of 0.236. However, the effect of education, training, and advertising costs on sales is insignificant. In addition, the analysis results also show that the regression model used has an accuracy rate of 58.7% which is explained by the independent variables. Companies can consider managing education, training, and promotion costs more effectively to increase their sales levels. Future research can involve other variables that affect sales and use a larger sample to obtain broader generalizations. Key words: Education and Training Costs, Promotion Costs, Sales